Exemplary Deterrent or Theatre of Martyrdom?: John Ogilvie's Execution and the Community of Glasgow - Goatman, Paul (Journal of Jesuit studies, 2020)
John Ogilvie's martyrdom in February 1615 should be seen in the context of a struggle for the hearts and minds of the people of Scotland between the Jesuit mission and James vi and i's government. Nowhere was this struggle more intense than within the town of Glasgow, where Ogilvie was imprisoned, tried and executed and which a large and influential Catholic community had long called home. Propaganda was disseminated by both sides during and after his trial and the archbishop of Glasgow, John Spottiswood, orchestrated its proceedings as a demonstration of royal and archiepiscopal power that involved local elites as well as central government officials. This article examines the events that took place in Glasgow during the winter of 1614-15 and provides a prosopographical analysis of the people involved. It makes the argument that, as had been the case during the Protestant Reformation of the 1540s and 1550s, Scotland's church and state mishandled Ogilvie's public ritual execution such that the local religious minority (now Catholics) became emboldened and more committed to Counter-Reformation.